Chemical and biological characterization of sulfated chitosan oligomer as heparin mimics. Issue 9 (November 2021) - Kocabay, Samet; Bahar, Mehmet Refik; Tekin, Suat; Akkaya, Recep; Akkaya, Birnur
In the present study, chitosan oligomer was modified to sulfated chitosan oligomer (ShCsO) to mimic heparin. Its chemical structure was determined by infrared spectroscopy (FT-IR), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis. The results showed that the FT-IR spectrum band at 799 cm −1 corresponds to C–O–S and that at 1212 cm −1 corresponds to S=O bond stretching, which prove that the sulfate groups are incorporated into chitosan oligomer successfully. The antimicrobial activity of ShCsO against to Bacillus subtilis in 1% concentration was 89.1 ± 1.7% . The IC50 (μg/ml) of ShCsO was 67.75, 56.07, 85.47, and 84.68 for A2780, MCF-7, DU-145, and HepG2, respectively. The results show that this newly synthesized material is a potential candidate to heparin-like chitosan derivatives. According to the literature, it was the first time that chitosan oligomer was modified to mimic heparin.